2016
DOI: 10.1111/jace.14087
|View full text |Cite
|
Sign up to set email alerts
|

Sintering of Ce, Sm, and Pr Oxide Nanorods

Abstract: Synthesis of CeO 2 , Pr 2 O 3 , and Sm 2 O 3 nanorods and their sintering have been investigated. In a strongly alkaline medium, nanorods of CeO 2 , Pr 2 O 3 , and Sm 2 O 3 were prepared from trivalent salts of rare earths (Ce, Pr, Sm) via precipitation synthesis. Nanorods were formed by nanocrystallites of fibrous structure, which were produced by the mechanism of selfarrangement of hexagonal particles of Re(III) hydroxides. The subsequent transformation of hydroxide into oxide proceeded via self-preservation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 45 publications
0
4
0
Order By: Relevance
“…[11][12][13][14] The above mentioned properties are typical of the tetragonal and cubic high-temperature phases: 1,12 this has stimulated a considerable effort in the characterization of the conditions determining zirconia phase stability and transition. 12,[15][16][17] The high-temperature phases can be stabilized at room temperature by introducing oxygen deficiencies; this is usually obtained by doping zirconia with divalent (Mg 2þ , Ca 2þ ) and trivalent (Y 3þ , Sc 3þ ) cationic species. 9 The phase stability of zirconia polymorphs is substantially different when one considers nanoparticles: in pure ZrO 2 nanopowders and nanocrystalline zirconia, the tetragonal phase (t-ZrO 2 ) and the cubic phase (c-ZrO 2 ) are stable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…[11][12][13][14] The above mentioned properties are typical of the tetragonal and cubic high-temperature phases: 1,12 this has stimulated a considerable effort in the characterization of the conditions determining zirconia phase stability and transition. 12,[15][16][17] The high-temperature phases can be stabilized at room temperature by introducing oxygen deficiencies; this is usually obtained by doping zirconia with divalent (Mg 2þ , Ca 2þ ) and trivalent (Y 3þ , Sc 3þ ) cationic species. 9 The phase stability of zirconia polymorphs is substantially different when one considers nanoparticles: in pure ZrO 2 nanopowders and nanocrystalline zirconia, the tetragonal phase (t-ZrO 2 ) and the cubic phase (c-ZrO 2 ) are stable at room temperature.…”
Section: Introductionmentioning
confidence: 99%
“…The studied NPs were produced with different ratios of CeCl 3 and TEA or TEMED. As a control, we used CeO 2 NPs produced by NH 4 OH precipitation and drying at 100 °C and two commercial preparations of CeO 2 from Cerion Advanced Materials with declared size <5 nm and CeO 2 from nGimat with declared size <25 nm.…”
Section: Resultsmentioning
confidence: 99%
“…In this work, we focused on the development of TEMED templated synthesis of NCH and compared its catalytic activities with TEA produced NCH, several commercially available CeO 2 NPs and also NPs produced by NH 4 OH precipitation and drying. [17] We have also studied the effects of detergents on phosphatase and haloperoxidase activity. In addition, a new fluorescent haloperoxidase assay was developed and used to detect CeO 2 NPs uptake in fixed cells.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies found that as the crystal size decreased with a lower Ce-O symmetry, the number of surface oxygen sites/oxygen vacancies in the CeO 2 sample increased [23]. In addition, thermal treatment at high temperatures could induce catalyst sintering [24], as is evidenced by the difference in the crystal sizes between PC-U and PC-T. However, compared to the remarkable increase of the crystal size from PC-U to PC-T, the slight change from PC-U to PC-PT suggested that the plasma might inhibit the catalyst sintering [25,26].…”
Section: Introductionmentioning
confidence: 99%